2019
DOI: 10.1590/1678-4162-10310
|View full text |Cite
|
Sign up to set email alerts
|

Bovine alphaherpesvirus 1 and 5 in semen from bulls presenting genital lesions under field conditions in Brazil

Abstract: Bovine alphaherpesviruses 1 and 5 (BoHV-1/5) are main pathogens of respiratory, reproductive and neurological diseases in cattle. The aim of this study was to investigate the frequency of neutralizing antibodies against BoHV-1/5 in serum samples and to detect viral DNA in semen of bulls from beef cattle farms located in RS. A total of 372 serum and semen sample from bulls were collected in eighteen farms. Serum samples were submitted to virus neutralization (VN) assay, while semen samples were used to detect B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The virus is secreted through nasal and eye secretions, placental fluid of aborted cattle, and semen (Rola et al, 2005). Regarding a study conducted on three bulls detected with BHV-1.5 in Brazil, it was found that BHV -1.5 was transmitted through nasal, ocular, genital contact (Henzel et al, 2019). The infectivity of BHV-1 remains stable during the storage of semen in liquid nitrogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus is secreted through nasal and eye secretions, placental fluid of aborted cattle, and semen (Rola et al, 2005). Regarding a study conducted on three bulls detected with BHV-1.5 in Brazil, it was found that BHV -1.5 was transmitted through nasal, ocular, genital contact (Henzel et al, 2019). The infectivity of BHV-1 remains stable during the storage of semen in liquid nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…This is related to good management in the farm so it was possible to impact BHV-1 shedding and enhance the immune system. The study of Henzel et al (2019) showed that two positive samples of BHV-1 PCR detection in bulls' semen in Brazil. Farms in Brazil have a history of nutritional and health management deficiencies, possibly favoring BHV-1 shedding in bull's semen.…”
Section: Resultsmentioning
confidence: 99%